2021
DOI: 10.1002/pmrj.12591
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a sacroiliac joint belt on function and pain using the active straight leg raise in pregnancy‐related pelvic girdle pain

Abstract: Introduction: Pelvic girdle pain (PGP) is the most common musculoskeletal concern in pregnancy. The Active Straight Leg Raise (ASLR) test is diagnostic. Sacroiliac joint (SIJ) belts are included in multimodal therapy, but there is no established predictive measure to determine which pregnant women will benefit. Objective: To determine if the ASLR score is immediately reduced by SIJ belt application and whether PGP pain and function improves after 4 weeks of belt use. Design: Prospective observational cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Compression garments targeting the lumbopelvic region are reported to reduce perceived symptoms of pain,108 109 incontinence110 111 and POP 112. One study in the general postpartum population found that SIJ belts were helpful in reducing pelvic girdle pain during performance of the Active Straight Leg Raise Test 113. In the general population with lumbopelvic pain, the effectiveness of SIJ belts is inconclusive and often described as having person-specific results 114–117.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compression garments targeting the lumbopelvic region are reported to reduce perceived symptoms of pain,108 109 incontinence110 111 and POP 112. One study in the general postpartum population found that SIJ belts were helpful in reducing pelvic girdle pain during performance of the Active Straight Leg Raise Test 113. In the general population with lumbopelvic pain, the effectiveness of SIJ belts is inconclusive and often described as having person-specific results 114–117.…”
Section: Resultsmentioning
confidence: 99%
“…112 One study in the general postpartum population found that SIJ belts were helpful in reducing pelvic girdle pain during performance of the Active Straight Leg Raise Test . 113 In the general population with lumbopelvic pain, the effectiveness of SIJ belts is inconclusive and often described as having person-specific results. [114][115][116][117] There is also no data on footwear and postpartum runners.…”
Section: Current Evidencementioning
confidence: 99%
“…One study of 46 women reported on a quantitative and qualitative assessment that pain intensity was decreased, and daily activities were easier with a pelvic support belt when used regularly 53 . These are safe, cost-effective, and easy to find options to include in the management of PRPGP in pregnancy 6,54 …”
Section: Managementmentioning
confidence: 99%
“…53 These are safe, cost-effective, and easy to find options to include in the management of PRPGP in pregnancy. 6,54…”
Section: Pelvic Support Beltsmentioning
confidence: 99%